Pengaruh Pemahaman Investasi, Modal Minimdal dan Kualitas Pelayanan Galeri Investasi Terhadap Minat Mahasiswa Berinvestasi di Pasar Modal (Studi Kasus Pada Mahasiswa Generasi Z) - Nadia Nor Rohma; Jeni Susyanti; Achmad Agus Priyono (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This study aims to determine the effect of understanding investment, minimum capital and service quality of investment galleries on student interest in investing in the capital market. The type of research used is quantitative research, with the method of data collection with the method of distributing questionnaires. The sample in this study were 91 respondents and data processing using the SPSS data processing program. This research has met the validity and reliability tests. The data analysis used in this study is the classical assumption test, multiple linear regression test, hypothesis testing and the coefficient of determination. The variables used in this study are understanding of investment, minimum capital and service quality of investment galleries, which are independent variables, while the dependent variable in this study is student interest in investing in the capital market. Keywords: Investment Understanding, Minimum Capital, Investment Gallery Service Quality.